2003
DOI: 10.1093/aob/mcg033
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Cereal Root Systems for Water and Nitrogen Capture: Towards an Economic Optimum

Abstract: A quantitative model of wheat root systems is developed that links the size and distribution of the root system to the capture of water and nitrogen (which are assumed to be evenly distributed with depth) during grain filling, and allows estimates of the economic consequences of this capture to be assessed. A particular feature of the model is its use of summarizing concepts, and reliance on only the minimum number of parameters (each with a clear biological meaning). The model is then used to provide an econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(186 citation statements)
references
References 23 publications
7
171
0
4
Order By: Relevance
“…Measurements of rooting have shown that the root length density of oilseed rape is greater than 1cm per cm 3 of soil within the top 40 cm of soil and averages 0.74 cm/cm 3 below 40cm depth (Blake et al, 2006). Studies on wheat have shown that a root length density of 1cm/cm 3 is required for the roots to extract all available water from soil (King et al, 2004). If this is the same for oilseed rape then its root system is generally not dense enough below 40 cm depth to extract all of the mineral N. If the root length density below 40 cm could be increased to 1cm/cm 3 then it is estimated that oilseed rape could take up an additional 8 kg N/ha using assumptions described in King et al (2004) and a typical mineral N content below 40 cm depth of 30 kg N/ha.…”
Section: Crop Traits To Improve N Use Efficiencymentioning
confidence: 99%
“…Measurements of rooting have shown that the root length density of oilseed rape is greater than 1cm per cm 3 of soil within the top 40 cm of soil and averages 0.74 cm/cm 3 below 40cm depth (Blake et al, 2006). Studies on wheat have shown that a root length density of 1cm/cm 3 is required for the roots to extract all available water from soil (King et al, 2004). If this is the same for oilseed rape then its root system is generally not dense enough below 40 cm depth to extract all of the mineral N. If the root length density below 40 cm could be increased to 1cm/cm 3 then it is estimated that oilseed rape could take up an additional 8 kg N/ha using assumptions described in King et al (2004) and a typical mineral N content below 40 cm depth of 30 kg N/ha.…”
Section: Crop Traits To Improve N Use Efficiencymentioning
confidence: 99%
“…In the Mediterranean Basin, one of the largest durum wheat producers in the world, more than 50 % of the total grain of durum wheat is produced in arid and semi-arid conditions, with severe drought most years (Loss and Siddique 1994;Araus et al 2003;García del Moral et al 2005). In dryland agricultural systems, a large root system that promotes access to soil water and nutrients is regarded as beneficial for plant growth (Richards 2008), although under terminal drought a greater investment in fine roots at depth would improve yield due to the better access to water and nitrogen (King et al 2003). Accordingly, root dry weight at depth has been related to drought adaptation (Lopes and Reynolds 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of nitrogen supply from subsoil layers is determined chiefly by crop demand for nitrogen, root morphological and physiological traits (King et al 2003), forms, amount and distribution of available N in a soil, and soil moisture (e.g. Svoboda et al 2000, Gastal and Lemaire 2002, Jeuffroy et al 2002.…”
mentioning
confidence: 99%